Utilisation of some of Plantation, Agro-forestry and Social Forestry Species for the Production of Dissolving Pulps - Madan, R. N.; Tandon, R. (Indian Forester, 1991)
Wood pulp or any other hlghly purified form of cellulose manufactured for commercial conversation into derivative is known as dissolvling pulp. The paper gives data on the proximate chemical analysis, bleaching and analysis of dissolving pulp produced from eucalyptus speceis, Pinus speceis, Sebania speceis, Moringa speceis, Prosopis juliflora, leucena leucocephaia and grevillea robusta. The dissolving pulps have been classified and characterised according to their and use. The general process of manufacturing of viscose rayon fibre from rayan grade pulps ha been described and the relsultsof commercial visoce rayon fibre are also gives for comparisons. The position of rayon grade pulp units in the country is given respect of raw material process and production.